Neural networks for vision, speech, and natural language - Linggard, R. (Robert) 1939-; Myers, D. J.; Nightingale, C. (BT telecommunications series, 1992)
This book is a collection of papers by British Telecom researchers and their BT funded academic collaborators in the BT Connex project. This project concerns the application of neural networks to image processing, speech technology and natural language processing.